2021
DOI: 10.22342/jme.12.2.12695.295-312
|View full text |Cite
|
Sign up to set email alerts
|

Buginese Ethnomathematics: Barongko Cake Explorations as Mathematics Learning Resources

Abstract: Mathematics is still viewed as a culture-free subject. This forms a negative perception for students on mathematics. Most students assume that mathematics and culture are not related. This may occur because mathematics taught in school is not contextual and far from the reality of everyday life. Historically, mathematics has become a part of everyday life. As a maritime nation, Indonesia has a diverse culture. But many teachers are not yet aware of the integration of the culture into mathematics learning. Baro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 20 publications
1
36
0
17
Order By: Relevance
“…Huda's research (2018) has also explored various shapes of traditional market snacks in Yogyakarta. The additional finding is also provided by Pathuddin et al (2021) focusing on the basic concepts of flat and space figures in the process of making barongko. Their result found that the process of making barongko cakes generates divisions, congruences, and similarities concept (Pathuddin et al, 2021).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Huda's research (2018) has also explored various shapes of traditional market snacks in Yogyakarta. The additional finding is also provided by Pathuddin et al (2021) focusing on the basic concepts of flat and space figures in the process of making barongko. Their result found that the process of making barongko cakes generates divisions, congruences, and similarities concept (Pathuddin et al, 2021).…”
Section: Resultsmentioning
confidence: 93%
“…Through contextual learning, students acquire a learning process involving cultural attributes. It can provide a comprehensive understanding for students (Pathuddin et al, 2021). Based on this research, exercises and problems can be developed as contextual learning for college students by using Buginese local food as a medium and GeoGebra as a tool.…”
Section: Buginese and Makassarese Traditional Foods As A Contextual Learning Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…According to Arisetyawan [2], the culture that exists in the environment of students has not been widely associated with the learning process. This culture can be seen in the mathematics learning that is learned at school is different from students' daily lives [3], [4]. So far, educators have not taken advantage of the student's environmental culture as a starting point for learning mathematics [5], [6].…”
Section: Introductionmentioning
confidence: 99%